Interne sosiale verantwoordelikheid as beeldhouer in organisies - Marco Roodt (Communicare)
Alvin Toffler from "Future Shock" (1982) fame may be regarded as the futurist who gave renewed impetus to social responsibility. Big business has marked social responsibility as a priority on their business agenda. Successful organisations, such as the Anglo-American Corporation, Barlows, Murray and Roberts, and food chains like Checkers and Pick-n-Pay realise that profits cannot be the sole aim of business anymore. The Southern African business environment is complex. It has numerous socio-economical and political problems. In order to survive in this environment, business needs a market Ing and business philosophy which Incorporates and solves these issues. People should be regarded as the most important as set of business. By practising social responsibility, business helps people to help themselves. A positive effect this has brought about is that it creates a favourable image of the organisation among external publics in society (Cutlip and Center, 1988). The question is whether the same principle can be applied to the building of positive images among employees in organisations. In other words, what about an internal form of social responsibility?